Contribution of Advertisement Tax to Makassar City Regional Original Income - Asdar, Asdar; Naidah, Naidah; Ms, Basuki Rahmat; Rusydi, Muhammad; Abu, A Fadli (Jurnal Ekonomi Balance, 2024)
This study aims to determine how big the contribution of advertising tax is to local revenue in the city of Makassar. The type of research used in this research is to use a qualitative approach in which the research is descriptive in nature. The data used in this study is quantitative, namely target data and realization of advertisement tax in 2013-2023 as well as primary data, namely data taken from interviews. The results of this study with descriptive analysis show that advertisement tax revenue in Makassar City is still not optimal. This can be seen from the contribution of advertisement tax to Regional Original Income in 2013-2023 which averaged only 2.72% or according to very low criteria, which was caused by a lack of public awareness in paying taxes and the Makassar mayor's regulation regarding the installation of advertisements that are no longer allowed to be carried out on national roads so as to reduce advertisement tax revenue